2020
DOI: 10.1111/tri.13575
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the association between older recipient age and outcomes after whole‐organ pancreas transplantation – a single‐centre, retrospective study

Abstract: Summary Older people are increasingly being referred for consideration for pancreas transplantation (PT). We investigated the outcomes after PT in our older recipient cohort. A prospectively maintained database was interrogated. The cohort was analysed for associations between outcome and older recipient age. A total of 444 transplants were performed in patients aged 23–54 years and 83 transplants in patients aged 55–67 years. There was no difference in death‐censored pancreas or kidney graft survival between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Old recipients in our cohort died more frequently from infection and malignancies but less frequently from cardiovascular events. These results are in line with other published studies [31,32] and might be attributed to our strict pretransplant cardiovascular assessment of pancreas transplant candidates with a low threshold for invasive cardiac evaluation, especially in older patients with a long history of diabetes in order to reduce the incidence of post‐transplant cardiac events [33] Despite significantly increased mortality, old recipients exhibited excellent pancreas and kidney graft survival rates that were equivalent to those of young recipients. Donor age, in our cohort, was not associated with increased risk of patient death.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Old recipients in our cohort died more frequently from infection and malignancies but less frequently from cardiovascular events. These results are in line with other published studies [31,32] and might be attributed to our strict pretransplant cardiovascular assessment of pancreas transplant candidates with a low threshold for invasive cardiac evaluation, especially in older patients with a long history of diabetes in order to reduce the incidence of post‐transplant cardiac events [33] Despite significantly increased mortality, old recipients exhibited excellent pancreas and kidney graft survival rates that were equivalent to those of young recipients. Donor age, in our cohort, was not associated with increased risk of patient death.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, three published studies demonstrated a correlation between recipient age and patient and/or graft survival: A recent single‐center study by the Oxford Transplant Centre [31] compared 83 transplants in patients aged 55 to 67 to 444 aged 23 to 54. While no difference in death‐censored kidney and pancreas graft survival was detected, the group reported, equivalent to our results, an inferior patient survival in old recipients (5 yrs., 89% vs 77%, 10 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, advanced age, in isolation, should not be considered an absolute exclusion criterion for SPKT. 38 - 41 Frailty is more common among older dialysis patients and kidney transplant recipients. 32 , 42 In our study of SPKT candidates and recipients, functional status distributions were fairly similar across age groups, such that reduced functional status was not solely a condition of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…9 There has been a growing body of literature evaluating outcomes of SPKT in older patients with DM. [10][11][12][13][14][15][16][17][18][19][20][21] Although "older" following kidney transplantation alone usually refers to patients in the age range of ≥65-70 years, [22][23][24][25][26] the definition of "older" following SPKT is considered to be an age range of ≥45-50 years. Although many transplant centers apply age limits of 45-50 years or less for SPKT consideration, there is currently no consensus on a strict chronological age cut-off for candidacy.…”
mentioning
confidence: 99%
“…In this "older" population, potential candidates need to undergo an extensive cardiovascular, peripheral vascular, psychosocial, and functional evaluation in an attempt to determine "physiologic age." [10][11][12][13][14][15][16][17][18][19][20][21][32][33][34][35][36][37][38] The majority of the literature has focused on assessing transplant outcomes in older compared to younger SPKT recipients. The purpose of this study was to retrospectively analyze our single-center experience in 255 SPKT recipients in the modern era (new millennium) in an ethnically diverse population and determine the effects, if any, that recipient age has on short and long-term outcomes.…”
mentioning
confidence: 99%